2018
DOI: 10.1177/1477971418791587
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of adult learners in a transition program

Abstract: Transition programs have emerged as a support for adult learners seeking college education. Adult learners' perspectives are missing in the literature on transition programs. To better support adult learners in transition programs, it is essential to understand their experiences and perspectives. Using Schlossberg's Transition Theory (Anderson, Goodman, & Schlossberg, 2012) and Cross's (1991) student barrier categorizations as a framework, this narrative study investigates the experiences of five adult learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Adult learners may choose to enroll in a community college because they are pursuing a program that leads to a vocational certificate or degree (Compton et al, 2006), but unfortunately, institutional processes and practices can pose challenges to their enrollment and academic credential completion (Osam et al, 2017). Decreasing barriers -like cost of attendance, admissions requirements, and course scheduling -is an opportunity for community colleges to relieve emotional burdens from adult learners who may also have additional hurdles to face as they return to school (Karmelita, 2018). In examining financial aid award processes, Osam and colleagues (2017) suggest colleges consider exploring ways to lessen the financial obligations of adult learners to support their return to college.…”
Section: Critical Questionsmentioning
confidence: 99%
“…Adult learners may choose to enroll in a community college because they are pursuing a program that leads to a vocational certificate or degree (Compton et al, 2006), but unfortunately, institutional processes and practices can pose challenges to their enrollment and academic credential completion (Osam et al, 2017). Decreasing barriers -like cost of attendance, admissions requirements, and course scheduling -is an opportunity for community colleges to relieve emotional burdens from adult learners who may also have additional hurdles to face as they return to school (Karmelita, 2018). In examining financial aid award processes, Osam and colleagues (2017) suggest colleges consider exploring ways to lessen the financial obligations of adult learners to support their return to college.…”
Section: Critical Questionsmentioning
confidence: 99%
“…they try to learn from the students as well'. Listening to the narratives of learners is important when reflecting upon transition processes as they are at the heart of the experience and enable practitioners to reflect on the support that is given during that process (Karmelita 2018). As Lave and Wenger (1991) argued in their Community of Practice theory, building relationships and communication with learners is essential throughout the transition process.…”
Section: Preparation-managing Expectationsmentioning
confidence: 99%
“…Specifically, transformation occurs as study abroad students create long-term goals for those experiences. Karmelita's (2018) phenomenological study on the experiences of five adult learners enrolled in a transition program at the university they were attending utilized Schlossberg's Transition Theory (1984) by applying the 4 S's to the transitions those students were experiencing. The findings illustrated that these students had a reliable support system because of the relationships they formed with other students in the transition program.…”
Section: Schlossberg's Transition Theorymentioning
confidence: 99%
“…As of 2019, the number of students studying abroad has more than doubled since 2000 (Institute for International Education, 2019). Even though enrollment had increased, however, research by Karmelita (2018) indicated that completion rates have not increased quite as rapidly. That is not necessarily the case for Sweden, though.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation